Factors Influencing the Effectiveness of a One-day CBT for Insomnia Workshop - Steele Ann; Lynch Seon; Shia Lin Brown June (Journal of Sleep And Sleep Disorder Research, 2015)
Insomnia is highly prevalent and has severe negative consequences. Cognitive Behavioural Therapy for Insomnia (CBT-I) is an evidence-based treatment that is usually delivered individually. Given the high prevalence, accessible one-day CBT-I workshops (each for up to 30 people) were developed to be run in the community for the general public 1. These CBT-I workshops have been found to reduce levels of insomnia 23 and are now run on a routine basis. As yet, little is known about the impact of factors such as co-morbid depression or anxiety, or receipt of previous treatment, on the effectiveness of the CBT-I workshop. This study aimed to evaluate the accessibility and clinical effectiveness of a series of nine one-day CBT-I workshops (n=120) run in routine practice and to explore the impact of factors including co-morbid depression or anxiety and receipt of previous treatment, on the effectiveness of the CBT-I workshops. The CBT-I workshops were found to be effective at reducing insomnia at one-month follow-up and broadly accessible across a wide group of people in the community. In addition, significant reductions in depression and anxiety were found and the severity of depression or anxiety at baseline did not interfere with the effectiveness of the workshop. People with no previous experience of counselling or psychological therapy showed greater reduction of insomnia symptoms. It is concluded that the CBT-I workshop is an accessible and effective treatment for insomnia across a range of clinical severity and complexity. Further benefits include reductions in both depression and anxiety.
Keywords: Insomnia